Strengthening prospective mathematics teachers’ geometry understanding through ethnomathematics integrated with generative artificial intelligence - Iyam Mariyati; Muhammad Sahdam Darmawan; Nurhayani Romeo (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2026)
This study aims to strengthen prospective mathematics teachers’ geometry understanding through ethnomathematics-based learning grounded in Papuan traditional houses integrated with Generative Artificial Intelligence (GenAI). A mixed-methods case study design with embedded quantitative data was employed involving 32 prospective teachers. Data were collected through geometry comprehension tests, ethnomathematical analysis rubrics, questionnaires, interviews, and observations, and analysed using descriptive statistics and thematic coding. The results show a significant increase in students’ mean scores from 58 to 80, alongside improved ability to connect geometric concepts with cultural structures. GenAI facilitated visualization, conceptual validation, and reflective thinking. This study contributes to the integration of ethnomathematics and generative technology as a culturally responsive and pedagogically meaningful approach in geometry education.